2021
DOI: 10.1002/acn3.51362
|View full text |Cite
|
Sign up to set email alerts
|

Early and late manifestations of neuropathy due to HSPB1 mutation in the Jewish Iranian population

Abstract: Objective: Mutations in the HSPB1 gene are associated with a distal hereditary motor neuropathy type 2 (dHMN2) or Charcot-Marie-Tooth disease type 2F (CMT2F), usually with autosomal dominant inheritance. This study aimed to describe the phenotype of the HSPB1 c.407G>T (p.Arg136Leu) mutation at early and late stages of the disease course. Methods: We identified this mutation (previously reported in patients from Italy) in a heterozygous state, among 14 individuals from eight families of Jewish Iranian descent. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…10 In recent years, a few familial and sporadic HMSN cases caused by rare site mutations have been reported due to the widespread use of gene sequencing technology. 11 This case study features a young man who initially had subtle lower limb weakness that progressively worsened. Over the course of seven months, he gradually noticed wasting in both lower limbs, beginning in the distal region.…”
Section: Genetic Test Results Are Reported Based On the Recommendatio...mentioning
confidence: 97%
“…10 In recent years, a few familial and sporadic HMSN cases caused by rare site mutations have been reported due to the widespread use of gene sequencing technology. 11 This case study features a young man who initially had subtle lower limb weakness that progressively worsened. Over the course of seven months, he gradually noticed wasting in both lower limbs, beginning in the distal region.…”
Section: Genetic Test Results Are Reported Based On the Recommendatio...mentioning
confidence: 97%
“…[8] With the widespread application of gene sequencing technology, some familial and sporadic HMSN cases caused by rare site mutations have been reported in recent years. [9] Studies have shown that HMSN is often accompanied by acute, subacute or chronic inflammatory responses, which can lead to an increase in oxidative stress and reactive oxygen species. Therefore, oxidative stress and neuroinflammation may be involved in the pathogenesis of HMSN.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] With the widespread application of gene sequencing technology, some familial and sporadic HMSN cases caused by rare site mutations have been reported in recent years. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…In the following years, studies and reports supplemented this conclusion [ 5 ]. The clinical phenotypes caused by HSPB1 gene mutation have certain heterogeneity in symptoms and onset age [ 6 ]. Even in the same family, clinical manifestations varied from muscle cramps as the only presenting symptom to a classic distal motor-sensory axonal neuropathy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%